The prospective study of laparoscopic finding in infertility cases - ., Shruti; Sen, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is a global reproductive health issue that affects many individuals and family. The aim of the present study was to evaluate the laparoscopic finding in infertility cases. Methods: Present study is a prospective study on laparoscopic evaluation of female infertility at Panna Dhai Mahila Chikitsalaya, Udaipur, Rajasthan, India. This study was done for the duration of one year from January 2017 to December 2017. Present study included total 100 cases randomly selected attending OBG OPD with both primary and secondary infertility. Results: Out of 100 cases infertile women 62 cases (62%) were of primary infertility and 38 cases (38%) were of secondary infertility. The mean duration of infertility was 3.7 years. Laparoscopic finding were as follow 42% had polycystic ovaries, 33% women had tubal pathology diagnosed on laparoscopy in which 22 women had tubal blocks diagnosed on chromopertubation and among them 19 had cornual block and 3 had ampullary block ,11% uterine finding and 7 women had adhesions in the pouch of douglas and one women had obliterated. About 20 women (20%) conceived during the period of study. Seven women had post laparoscopic complication two women complained of shoulder pain and another four of abdominal pain post operatively. Conclusions: Laparoscopy is the gold standard for diagnosing tubal factors, peritoneal factors, endometriosis and adhesions, because no other imaging technique provides the same degree of sensitivity and specificity and it should be considered in infertility workup for early treatment decision.